The impact of the federal elections on the transformation of the Canadian Party System In 1990-2020 years - Andrey N. Komarov (RUDN Journal of World History)
The study presents the evolution of the Canadian party system in the period from 1993 to 2021. The author believes that the results of the general elections in Canada, from 1993 to 2021, had the most direct impact on the transformation of the party system of this state, forming its parliamentary multiparty system at the national level. According to the author, it is worth highlighting three immediate periods of evolution of the Canadian party system: from 1993 to 2006, from 2006 to 2015, and from 2015 to 2019. According to the author, this periodization reflected not only the evolution of the party system within the framework of Canadian parliamentarism, but also changes in political ideologies themselves. The author emphasizes that the 1993 parliamentary elections were the most important milestone in the entire transformation of the Canadian party system, forming new regional parties in the Canadian parliament. The study notes that the 2006 parliamentary elections were extremely important, since the Conservative Party won the elections for the first time, providing a significant alternative to the liberals. The results of the parliamentary elections were no less significant in terms of influence on the development of leading political ideologies in Canada. The author concludes that the results of the parliamentary elections had the most direct impact on the change of political leadership in the parties. This is indicative of the examples of S. Harper, who led the Conservatives to victory in the 2006 elections, as well as J. Trudeau, who overcame the crisis of liberalism and won the 2015 elections. From the author’s point of view, the elections changed the political landscape, contributed to the strengthening of some parties and the disappearance of others.